Code Switching and Code Mixing in Indonesian Language Learning for Foreign Speakers (BIPA) Universitas Komputer Bandung - Majid, Muhamad Nurkolis; Zulkarnain, Yulianur (Departement of Arabic Language and Literature, 2025)
UNIKOM has become a crucial center for international students learning Indonesian as a Foreign Language (BIPA). The specially designed BIPA program, with experienced instructors, ensures effective learning. UNIKOM’s multicultural environment enriches the educational experience and accelerates cultural adaptation. The program also teaches Indonesian culture, providing essential insights for international students' studies and lives in Indonesia. However, using Indonesian as a second language often leads to language errors, primarily influenced by the students’ dominant mother tongues. This research aims to explore the sociolinguistic phenomena in bilingual learning environments and identify the causes and purposes of these occurrences. The research employs a qualitative descriptive method. Data collection techniques include observation and conversation, utilizing participant observation, recording, and note-taking. Data were naturally gathered during the BIPA learning process. The findings reveal sociolinguistic phenomena such as code-switching and code-mixing. Researchers identified 21 sociolinguistic instances, divided into two categories: 14 instances of code-mixing 10 involving Indonesian to English and 4 from Indonesian to Arabic and 7 instances of code-switching 5 from Indonesian to English and 2 from Indonesian to Arabic. The study reveals that code-mixing and code-switching in BIPA classes at UNIKOM serve to enhance understanding between students and instructors, facilitating inquiries and explanations for terms unfamiliar in students’ native languages.